Henry Tudor administrates The Throne Of England In (1485AD) (Journal of the College of Education for Women, 2019)
The Era of Henry VII is the king who established the Tudor as they ruled England for(24) years .He made drasfic changes in British Economy and the state of the country wasstable and secure.Thes economic achievement of make him Qualified to be called The founder of themodern English History .On the basis of that significance to study one of the development stages of one of thedeveloped societies presently, i.e. the English society, this thesis came under the title (TheInternal Policy in England 1509-1547) to examine the overall political, economic and socialpositions England passed through. The thesis also indicated the intensive labor state sufferedby the English society with all its sections, especially the intellectuals class who faced variouskinds of elimination, fighting and torture which led to losing their lives.